Fatigue of glued-in rods in engineered hardwood products — Part II: Numerical modelling. Issue 5 (1st June 2019) - Myslicki, S.; Walther, F.; Bletz-Mühldorfer, O.; Diehl, F.; Lavarec, C.; Beber, V. C.; Vallée, T.
ABSTRACT: Fatigue behaviour of materials is traditionally performed on probes that ensure that stresses (or strains) are very uniform. This is a situation seldom encountered in most adhesively bonded joints, where stresses usually peak at the end of the overlaps. This paper presents a relatively simple model to predict the fatigue behaviour of glued-in rods (GiR) involving hardwood in previously investigated in an extensive experimental campaign. The model is based on strength and stiffness degradation of the components of the GiR, which were experimentally estimated in small scale tests. Based thereupon, Finite Element Analysis (FEA) was used to estimate the effect of material degradation on the residual strength of the GiR, which was then interpreted as S-N-curves. The influence of several parameters, e.g. strength and stiffness degradation rates and the magnitude of the residual strength threshold were numerically investigated. The result showed that it is possible, using a practitioner adapted numerical model, to predict the fatigue behaviour of GiR, based upon comparatively simple fatigue characterisation on their components.